2017
DOI: 10.3892/etm.2017.4828
|View full text |Cite|
|
Sign up to set email alerts
|

MiR-203 inhibits estrogen-induced viability, migration and invasion of estrogen receptor α-positive breast cancer cells

Abstract: Abstract. Breast cancer is common in females, and accounts for a large proportion of cancer-related cases of mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…To more directly interrogate the relationship between collagen architecture, stromal stiffness, and epithelial density, as well as to rule out potentially confounding effects of age, parity, behavior of human breast cancer cells, were repressed both in the MCF10A MECs cultured on the stiff PA gels and as 3D preassembled acini embedded within a ribose-stiffened BM/collagen gel ( Figure 5, E-H). We focused on miR-203 for further analysis because of its prior role in restricting breast cancer progression and its implicated role in breast cancer risk (38,(50)(51)(52)(53)(54). Consistently, miR-203 expression levels significantly decreased in the freshly isolated primary murine mammary organoids embedded within the ribose-stiffened BM/collagen gels ( Figure 5I).…”
Section: Resultsmentioning
confidence: 74%
“…To more directly interrogate the relationship between collagen architecture, stromal stiffness, and epithelial density, as well as to rule out potentially confounding effects of age, parity, behavior of human breast cancer cells, were repressed both in the MCF10A MECs cultured on the stiff PA gels and as 3D preassembled acini embedded within a ribose-stiffened BM/collagen gel ( Figure 5, E-H). We focused on miR-203 for further analysis because of its prior role in restricting breast cancer progression and its implicated role in breast cancer risk (38,(50)(51)(52)(53)(54). Consistently, miR-203 expression levels significantly decreased in the freshly isolated primary murine mammary organoids embedded within the ribose-stiffened BM/collagen gels ( Figure 5I).…”
Section: Resultsmentioning
confidence: 74%
“…Two of the previous studies reported miR-203 as an oncogene, as silence of its expression inhibited breast cancer cells colony formation, transformation, stemness and migration [21,37]. Others suggested miR-203 as an anti-oncogene through performing in vitro experiments [22,38,39]. This contradiction may due to the different cell lines used and the difference in testing parameters.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, decreased levels of miR-497 participate in the cell proliferation, migration, and invasion of ER-negative breast cancer by targeting ERα [67]. Conversely, miR-203 suppresses the estrogen-induced viability, migration and invasion of ERα-positive breast cancer cells [68]. miR-107-5p has a direct interaction with ESR1 to enhance the proliferation and invasion of endometrial carcinomas [69].…”
Section: Mirnas and Er Function In Cancersmentioning
confidence: 99%